Flame-retardant light-weight high-sound-insulation composite PVC wiredrawing cloth and preparation method thereof
By optimizing material formulation and structural design, and using flame-retardant modified hollow glass microspheres and precision hot pressing process, multi-layer composite materials are formed, which solves the shortcomings of PVC high-gap materials in terms of flame retardancy, lightweight and sound insulation performance, and realizes the multi-functional needs of high-end application scenarios.
Patent Information
- Application Number
- CN202511154405.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2025-12-02
AI Technical Summary
Existing PVC high-density materials have shortcomings in flame retardancy, lightweighting, and sound insulation, which limits their promotion in high-end application scenarios.
By optimizing material formulation and structural design, using flame-retardant modified hollow glass microspheres, polyester fabric treated with cyclophosphonitrile flame retardant, and precision hot pressing process, a sandwich structure of dense functionalized PVC surface layer/strong adhesive intermediate layer/flame-retardant dense fabric bottom layer is formed. Combined with multi-level protection and low-density hollow glass microspheres, the flame retardancy, lightweight and sound insulation effects are improved.
It achieves a comprehensive improvement in flame retardancy, lightweighting and sound insulation performance, meeting the multifunctional needs of high-end application scenarios. The material exhibits excellent performance in terms of thermal-oxygen barrier, sound wave reflection dissipation and damping conversion.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, and in particular to a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric and its preparation method. Background Technology
[0002] High-density PVC materials, due to their unique spacer structure, possess advantages such as high strength, heat insulation, good impact resistance, and waterproofing, and are widely used in outdoor advertising, awnings, tarpaulins, and industrial packaging. However, with the increasing complexity of usage environments and higher performance requirements, existing high-density PVC materials still have certain shortcomings in flame retardancy, lightweighting, and sound insulation, limiting their further promotion in high-end application scenarios.
[0003] CN115008863B discloses a production process for impact-resistant PVC filament coating. This process involves preparing a pre-emulsion using styrene and 1-allyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, and then polymerizing the pre-emulsion with vinyl chloride monomer to generate grafted polyvinyl chloride. Polyester filament is then used as the base yarn and filament coating material to produce a PVC filament coating material with good impact resistance and weather resistance. However, this technical solution primarily focuses on the material's impact resistance and weather resistance, without addressing the improvement of flame retardant properties. Furthermore, the overall weight of the material is relatively large, making it difficult to meet lightweight requirements. In addition, this solution does not optimize sound insulation performance, limiting its application in scenarios requiring high sound insulation. CN114808598B discloses a drone runway and laying device made of high-pressure airtight filament fabric. Through a multi-layered structural design, including a filament base fabric, a PVC interlayer, a machine-made mesh, and a PVC surface layer, a high-pressure airtight filament fabric material is formed, suitable for high-intensity applications such as drone runways. However, while this technical solution improves the material's mechanical strength and impact resistance, it does not adequately consider optimizing flame retardancy and sound insulation performance. Furthermore, due to its multi-layered composite structure, the material is relatively heavy, making it difficult to meet lightweight requirements. In addition, this solution pays little attention to sound insulation performance, making it less effective in addressing noise pollution issues.
[0004] The above problems indicate that existing PVC high-density materials still have significant shortcomings in terms of flame retardancy, lightweighting, and sound insulation. Summary of the Invention
[0005] To overcome the above deficiencies, this invention provides a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric and its preparation method. By optimizing the material formulation and structural design, the flame-retardant performance of the material is improved, the overall weight is reduced, and the sound insulation effect is enhanced, thereby meeting the demand of high-end application scenarios for high-performance PVC high-sound-insulating materials.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] This invention also discloses a method for preparing a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric, comprising the following steps:
[0008] Step S1: By weight, add 80-100 parts PVC resin powder, 10-15 parts nitrile rubber, 5-10 parts plasticizer dioctyl adipate, 3-5 parts barium zinc stabilizer, 0.5-1 part antioxidant 1010, 0.2-0.5 parts ultraviolet absorber UV-531, 0.2-0.4 parts antifungal and antibacterial agent, 0.2-0.4 parts acrylate processing aid ACR-201, and 0.5 parts... -1 part calcium stearate lubricant, 5-10 parts rutile titanium dioxide R-298, 0.5-1 part pigment phthalocyanine blue BGS, 5-10 parts flame retardant modified hollow glass microspheres, 1.0-1.5 parts vulcanizing agent dicumyl peroxide, 1.5-2.0 parts activator zinc oxide, 0.8-1.2 parts accelerator triallyl isocyanurate are mixed, calendered, cooled, trimmed and rolled to obtain the surface PVC film layer;
[0009] Step S2: Mix 80-120 parts of EPVC paste resin PCH-31, 50-70 parts of plasticizer TOTM and 40-50 parts of adhesive at high speed to form a paste slurry, and obtain the bottom adhesive slurry.
[0010] Step S3: Impregnate the flame-retardant polyester woven fabric with cyclophosphonitrile flame retardant solution, dry it and gain 8-10% weight, then coat its surface with a base adhesive paste, and dry it to obtain PVC coated flame-retardant polyester woven fabric.
[0011] Step S4: Apply the surface PVC film layer and the PVC-coated flame-retardant polyester woven fabric coated with the bottom adhesive paste to the surface, hot press and laminate, and form a brushed texture to obtain a flame-retardant, lightweight, and high-sound-insulating composite PVC brushed fabric.
[0012] Preferably, the mixing process includes three stages:
[0013] First stage: PVC resin, nitrile rubber, plasticizer, stabilizer, antioxidant, ultraviolet absorber, mildew and antibacterial agent, processing aid and lubricant are mixed at 80-100℃ for 3-5 minutes and cooled to 60-70℃;
[0014] The second stage involves adding flame-retardant modified hollow glass microspheres, titanium dioxide, and pigments, stirring until homogeneous, and then heating to 110-120℃. This is mainly to prevent the flame-retardant coating layer on the surface of the microspheres from being damaged by high temperature or mechanical shear.
[0015] Third stage: Add the remaining components and mix at 150-160℃ for 5-10 minutes. Then cool down to 100-120℃, add flame-retardant modified hollow glass microspheres, stir evenly, and immediately transfer to the calendering process.
[0016] Throughout the process, a safe temperature window is maintained to protect the integrity of the microsphere structure and ensure the uniform formation of the cross-linked network. The process is then immediately transferred to the calendering process to prevent pre-cross-linking from affecting the film quality.
[0017] As a preferred method, the synthesis method of the antifungal and antibacterial agent in step S1 is as follows: 0.9-1.1 mol of phthalimide is dissolved in 550-650 mL of dichloromethane, 1-1.1 mol of trichloromethylsulfonyl chloride is slowly added dropwise while controlling the temperature at ≤10℃, 1-1.1 mol of triethylamine is added, the temperature is raised to 23-28℃, the reaction is carried out for 5-6 hours, the mixture is filtered and concentrated, and then recrystallized with ethanol to obtain the antifungal and antibacterial agent.
[0018] As a preferred method, the preparation method of flame-retardant modified hollow glass microspheres in step S1 is as follows: immerse 20-100 μm hollow glass microspheres in 5-8wt% sodium hydroxide solution and ultrasonically vibrate at 60-70℃ for 15-20 min to remove surface oil stains, then transfer them to 8-10% hydrochloric acid solution and soak at room temperature for 30-40 min to activate silanol groups, centrifuge and wash with deionized water until the water conductivity is ≤5μS / cm, and then vacuum dry at 60-80℃ for 2-3 h to obtain surface-activated hollow glass microspheres;
[0019] Next, a flame-retardant layer is constructed. By weight, 15-20 parts of ammonium polyphosphate, 5-8 parts of aluminum hypophosphite solution, and 40-60 parts of ethanol are dissolved in 100 parts of deionized water to prepare an atomizing agent. The surface-activated hollow glass microspheres are dynamically coated three times in a fluidized bed at an inlet air temperature of 70±2℃ and an atomization pressure of 0.3-0.35MPa (with a 5-minute drying interval between each coating). Then, the microspheres are heat-treated at 100-110℃ for 30-40 minutes to form a 0.5-1.0 μm thick flame-retardant coating layer, thus obtaining flame-retardant grafted hollow glass microspheres.
[0020] Finally, surface modification was carried out by spraying flame-retardant grafted hollow glass microspheres in a fluidized bed with an anhydrous ethanol solution containing 2-3% titanate coupling agent and reacting at 60-70℃ for 20-30 min to obtain flame-retardant modified hollow glass microspheres.
[0021] Preferably, the adhesive in step S3 is prepared as follows:
[0022] 100 parts of chlorinated polypropylene HCPP-030 with a chlorine content of 28-32%, 8-12 parts of maleic anhydride, and 0.3-0.7 parts of dicumyl peroxide are melt-mixed in an internal mixer at 135-150°C, and then extruded and granulated to obtain an adhesive.
[0023] Preferably, the flame-retardant polyester woven fabric has a pore size ≤0.05mm and a basis weight of 100-500g / m². 2 .
[0024] Preferably, the hot-pressing composite process conditions are: 120-160℃, 0.5-5.0MPa hot pressing for 30-60s.
[0025] Preferably, the hot-pressing composite process is a segmented pressurization process: the pre-pressing stage is carried out at a pressure of 0.5-1MPa for 10-20s to remove interlayer bubbles; the final pressing stage is carried out at a pressure of 3-5.0MPa for 20-40s.
[0026] As a preferred option, the process for forming the brushed texture is as follows: embossing with a parallel stripe embossing roller at 80-150℃ and 8-15MPa, with a texture depth ≥0.1mm, followed by cooling to 40℃, trimming the edges and winding up to obtain a flame-retardant, lightweight, high-sound-insulating composite PVC brushed fabric.
[0027] This invention, through optimized material formulation and structural design, exhibits superior performance in various application scenarios. Whether it's flame retardancy, lightweight design, or sound insulation, all are achieved through scientifically sound processes and material selection, providing reliable technical support for high-end applications.
[0028] The flame-retardant, lightweight, and high-sound-insulating composite PVC filament fabric disclosed in this invention is prepared based on a layered functionalization and precision composite process. First, a functionalized surface PVC film layer is prepared through a intensive mixing and calendering process: PVC resin powder is blended with nitrile rubber to improve flexibility and damping properties; plasticizer dioctyl adipate, barium zinc stabilizer, antioxidant, UV absorber, antifungal and antibacterial agent, processing aid ACR-201, lubricant, pigment, and core functional filler—hollow glass microspheres with a surface specially modified for flame retardancy and coupled with titanate (NDZ-201)—are added; and a cross-linked network is constructed using vulcanizing agent dicumyl peroxide, activator zinc oxide, and accelerator TAIC to enhance strength; secondly, EP… VC paste resin, high-temperature resistant plasticizer TOTM, and a self-made adhesive containing strong polar anhydride groups are mixed at high speed to form a high-adhesion bottom slurry. At the same time, flame-retardant polyester woven fabric is impregnated with cyclophosphonitrile flame retardant and coated with the bottom slurry. Finally, the surface PVC film layer and the coated flame-retardant fabric are firmly bonded together through a precisely controlled segmented hot pressing process (pre-pressing for degassing and final pressing for compaction). Simultaneously, the embossing roller is used to form a high-temperature and high-pressure drawing texture, ultimately forming a sandwich structure composite material of "dense functional PVC surface layer / strong adhesive middle layer / flame-retardant dense fabric bottom layer".
[0029] The superior performance of this invention stems from the functional synergy of its components and the meticulous structural design. Flame retardancy is achieved through multi-level protection: the polyester fabric treated with cyclophosphonitrile flame retardant provides phosphorus-nitrogen gas-phase flame retardancy and inhibits dripping; the ammonium polyphosphate / aluminum hypophosphite coating on the surface of the flame-retardant modified hollow glass microspheres in the surface film is catalyzed by heat to form char and release flame-retardant gases, while its silica shell and dense flame-retardant coating layer constitute a thermal-oxygen barrier; barium-zinc stabilizers inhibit the thermal decomposition of PVC; and the bottom dense fabric forms a physical flame barrier layer with the surface film. The core of lightweighting lies in the replacement of solid fillers with low-density hollow glass microspheres (with an internal hollow structure). Their surfaces are etched and activated, dynamically coated with a flame-retardant layer in a fluidized bed, and treated with coupling agents. This achieves functionalization and enhances the interfacial bonding with the matrix while strictly protecting the integrity of the microspheres, synergistically reducing resin density through the dioctyl adipate / TOTM plasticizing system. The sound insulation performance integrates the sound wave reflection and dissipation at multiple interfaces (e.g., impedance mismatch between the surface high-density film and the underlying porous fabric), the damping conversion within the material (e.g., energy dissipation due to molecular friction enhanced by flexible segments and cross-linked networks of nitrile rubber), the Helmholtz resonance sound absorption of hollow glass microspheres (20-100μm cavity dissipates high-frequency sound), and the sound absorption effect of the microporous structure of flame-retardant fabric, resembling a micro-perforated plate structure. These properties mutually reinforce each other: the flame-retardant microspheres contribute both lightweight and sound insulation; the dense flame-retardant fabric serves as both a sound insulation and flame-retardant barrier; and the strong bonding interface (chemical bonding and segmented hot pressing ensure stable and coordinated operation of the multi-layer structure, ultimately achieving an integrated performance of flame retardancy, lightweight, and high sound insulation.
[0030] This solution also proposes a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric prepared by the above preparation method.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] 1. This solution achieves synergistic effects of multiphase materials in its component design. By constructing a rigid-flexible matrix network and finely coupling functional components, it overcomes the performance limitations of traditional single-phase systems. The molecular chains of nitrile rubber and PVC resin form an interpenetrating network through plasticizer bridging, maintaining chain mobility even at low temperatures. Meanwhile, flame-retardant modified microspheres establish a stable interface with the polymer matrix through surface chemical modification, and their hollow structure enhances the material's energy dissipation efficiency at the microscale through a multiple sound wave scattering mechanism. The combined design of stabilizers and protective components forms an antioxidant-UV protection system at the molecular level, while the slow release mechanism of the antibacterial agent extends the material's service stability. The entire component system achieves a balance between contradictory performance characteristics at the thermodynamic and kinetic levels, meeting the requirements for high weather resistance and multifunctional integration.
[0033] 2. The process design mainly takes into account the characteristics of the raw materials. This solution introduces a mixing process to better and more uniformly integrate the components. By controlling the process and temperature, the uniformity of the components in the surface PVC film layer is ensured, and the peeling between components is avoided. During the lamination process, attention is also paid to the control of key process parameters such as temperature and pressure, which not only ensures the lamination effect of the flame-retardant, lightweight, and high-sound-insulating composite PVC fabric, but also prevents the breakage of hollow glass microspheres, ensuring the effectiveness of the function. Detailed Implementation
[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0035] General Implementation Examples
[0036] A method for preparing a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric includes the following steps:
[0037] Step S1: By weight, mix 80-100 parts PVC resin powder, 10-15 parts nitrile rubber, 5-10 parts plasticizer dioctyl adipate, 3-5 parts barium zinc stabilizer, 0.5-1 part antioxidant 1010, 0.2-0.5 parts ultraviolet absorber UV-531, 0.2-0.4 parts mildew and antibacterial agent, 0.2-0.4 parts acrylate processing aid ACR-201, 0.5-1 part calcium stearate lubricant, 5-10 parts rutile titanium dioxide R-298, 0.5-1 part pigment phthalocyanine blue BGS, 5-10 parts flame-retardant modified hollow glass microspheres, 1.0-1.5 parts vulcanizing agent dicumyl peroxide, 1.5-2.0 parts activator zinc oxide, and 0.8-1.2 parts accelerator triallyl isocyanurate in three stages of intensive mixing.
[0038] First stage: PVC resin, nitrile rubber, plasticizer, stabilizer, antioxidant, ultraviolet absorber, mildew and antibacterial agent, processing aid and lubricant are mixed at 80-100℃ for 3-5 minutes and cooled to 60-70℃;
[0039] Second stage: Add titanium dioxide and pigments, stir evenly, and then heat to 110-120℃; this is mainly to avoid damage to the flame-retardant coating layer on the surface of the microspheres due to high temperature or mechanical shear.
[0040] Third stage: Add the remaining components and mix at 150-160℃ for 5-10 minutes. Then cool down to 100-120℃ and add flame-retardant modified hollow glass microspheres. Stir evenly and immediately transfer to the calendering process. Calender, cool, trim and roll to obtain the surface PVC film layer.
[0041] Step S2: Mix 80-120 parts of EPVC paste resin PCH-31, 50-70 parts of plasticizer TOTM and 40-50 parts of adhesive at high speed to form a paste slurry, and obtain the bottom adhesive slurry.
[0042] Step S3: For materials with a pore size ≤ 0.05 mm and a basis weight of 100-500 g / m³... 2 Flame-retardant polyester woven fabric is impregnated with cyclophosphonitrile flame retardant solution, and after drying, the weight gain is 8-10%. Then, a base adhesive slurry is coated on its surface, and after drying, PVC-coated flame-retardant polyester woven fabric is obtained.
[0043] Step S4: Apply the PVC film layer to the surface of the PVC-coated flame-retardant polyester woven fabric coated with the bottom adhesive paste, and hot-press the composite. The hot-pressing process is segmented: the pre-pressing stage is maintained at 0.5-1MPa for 10-20s to remove interlayer air bubbles; the final pressing stage is maintained at 3-5.0MPa for 20-40s to form a brushed texture. Use a parallel stripe embossing roller at 80-150℃ and 8-15MPa to emboss the texture, with a texture depth ≥0.1mm. Then cool to 40℃, trim the edges and roll up to obtain a flame-retardant, lightweight, high-sound-insulating composite PVC brushed fabric.
[0044] The method for synthesizing the antifungal and antibacterial agent in step S1 is as follows: 0.9-1.1 mol of phthalimide is dissolved in 550-650 mL of dichloromethane, and 1-1.1 mol of trichloromethylsulfonyl chloride is slowly added dropwise while controlling the temperature at ≤10℃. Then, 1-1.1 mol of triethylamine is added, the temperature is raised to 23-28℃, and the reaction is carried out for 5-6 hours. After filtration and concentration, the mixture is recrystallized with ethanol to obtain the antifungal and antibacterial agent.
[0045] The preparation method of flame-retardant modified hollow glass microspheres in step S1 is as follows: 20-100 μm hollow glass microspheres are immersed in 5-8wt% sodium hydroxide solution and ultrasonically vibrated at 60-70℃ for 15-20 min to remove surface oil stains. Then, they are transferred to 8-10% hydrochloric acid solution and soaked at room temperature for 30-40 min to activate the silanol groups. After centrifugation and washing with deionized water until the water conductivity is ≤5 μS / cm, they are vacuum dried at 60-80℃ for 2-3 h to obtain surface-activated hollow glass microspheres.
[0046] By weight, 15-20 parts of ammonium polyphosphate, 5-8 parts of aluminum hypophosphite solution, and 40-60 parts of ethanol are dissolved in 100 parts of deionized water to prepare an atomizing agent. The surface-activated hollow glass microspheres are dynamically coated three times in a fluidized bed at an inlet air temperature of 70±2℃ and an atomization pressure of 0.3-0.35MPa (with a 5-minute drying interval between each coating). Then, the microspheres are heat-treated at 100-110℃ for 30-40 minutes to obtain flame-retardant grafted hollow glass microspheres.
[0047] Flame-retardant grafted hollow glass microspheres were spray-treated in a fluidized bed with an anhydrous ethanol solution containing 2-3% titanate coupling agent NDZ-201 and reacted at 60-70℃ for 20-30 min to obtain flame-retardant modified hollow glass microspheres.
[0048] The method for preparing the adhesive in step S3 is as follows:
[0049] 100 parts of chlorinated polypropylene HCPP-030 with a chlorine content of 28-32%, 8-12 parts of maleic anhydride, and 0.3-0.7 parts of dicumyl peroxide are melt-mixed in an internal mixer at 135-150°C, and then extruded and granulated to obtain an adhesive.
[0050] Example 1
[0051] A method for preparing a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric includes the following steps:
[0052] Step S1: By weight, mix 80 parts PVC resin powder, 10 parts nitrile rubber, 5 parts plasticizer dioctyl adipate, 3 parts barium zinc stabilizer, 0.5 parts antioxidant 1010, 0.2 parts ultraviolet absorber UV-531, 0.2 parts antifungal and antibacterial agent, 0.2 parts acrylate processing aid ACR-201, 0.5 parts calcium stearate lubricant, 5 parts rutile titanium dioxide R-298, 0.5 parts pigment phthalocyanine blue BGS, 5 parts flame-retardant modified hollow glass microspheres, 1.0 part vulcanizing agent dicumyl peroxide, 1.5 parts activator zinc oxide, and 0.8 parts accelerator triallyl isocyanurate in three stages of intensive mixing.
[0053] First stage: PVC resin, nitrile rubber, plasticizer and additives are mixed at 80°C for 3 minutes and then cooled to 60°C;
[0054] Second stage: Add flame-retardant modified hollow glass microspheres, rutile titanium dioxide R-298 and pigment phthalocyanine blue BGS, stir evenly and heat to 110℃.
[0055] Third stage: Add the remaining components and mix at 155℃ for 8 minutes. Then cool down to 110℃ and add flame-retardant modified hollow glass microspheres. Stir evenly and immediately transfer to the calendering process. Calender, cool, trim and roll to obtain the surface PVC film layer.
[0056] Step S2: Mix 80 parts of EPVC paste resin PCH-31, 50 parts of plasticizer TOTM and 40 parts of adhesive at high speed to form a paste slurry, and obtain the bottom adhesive slurry.
[0057] Step S3: Prepare a sample with a pore size of 0.05 mm and a basis weight of 100 g / m³. 2 Flame-retardant polyester woven fabric is impregnated with cyclophosphonitrile flame retardant solution, and after drying, the weight increases by 8%. Then, a base adhesive slurry is coated on its surface, and after drying, PVC-coated flame-retardant polyester woven fabric is obtained.
[0058] Step S4: Apply the PVC film layer to the surface of the PVC-coated flame-retardant polyester woven fabric coated with the bottom adhesive paste, and hot-press the composite. The hot-pressing process is segmented pressure: the pre-pressing stage is at 0.5MPa pressure for 10s; the final pressing stage is at 3.0MPa pressure for 20s; use a parallel stripe embossing roller to emboss at 80℃ and 8.0MPa, with a texture depth of 0.1mm, then cool to 40℃, trim the edges and roll up to obtain a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric.
[0059] The method for synthesizing the antifungal and antibacterial agent in step S1 is as follows: 0.9 mol of phthalimide is dissolved in 550 mL of dichloromethane, 1.0 mol of trichloromethylsulfonyl chloride is slowly added dropwise, and the temperature is controlled to be less than or equal to 10 °C. 1.0 mol of triethylamine is added, the temperature is raised to 23 °C, the reaction is carried out for 5 h, the mixture is filtered and concentrated, and then recrystallized with ethanol to obtain the antifungal and antibacterial agent.
[0060] The preparation method of flame-retardant modified hollow glass microspheres in step S1 is as follows: 20-100μm hollow glass microspheres are immersed in 5% sodium hydroxide solution and ultrasonically vibrated at 60℃ for 15min to remove surface oil stains. Then, they are transferred to 8% hydrochloric acid solution and soaked at room temperature for 30min to activate the silanol groups. After centrifugation and washing with deionized water until the conductivity of water is less than or equal to 5μS / cm, they are vacuum dried at 60℃ for 2h to obtain surface-activated hollow glass microspheres.
[0061] By weight, 15 parts ammonium polyphosphate and 5 parts aluminum hypophosphite were dissolved in 100 parts deionized water and 40 parts ethanol to prepare an atomizing agent. The surface-activated hollow glass microspheres were dynamically coated three times in a fluidized bed at an inlet air temperature of 70°C and an atomization pressure of 0.3 MPa, with a drying interval of 5 minutes between each coating. The microspheres were then heat-treated at 100°C for 30 minutes to obtain flame-retardant grafted hollow glass microspheres.
[0062] Flame-retardant grafted hollow glass microspheres were spray-treated in a fluidized bed with an anhydrous ethanol solution containing 2.0% by mass of titanate coupling agent NDZ-201 and reacted at 60℃ for 20 min to obtain flame-retardant modified hollow glass microspheres.
[0063] The method for preparing the adhesive in step S3 is as follows:
[0064] 100 parts of chlorinated polypropylene HCPP-030 with a chlorine content of 28%, 8 parts of maleic anhydride, and 0.3 parts of dicumyl peroxide were melt-mixed in an internal mixer at 135°C, and then extruded and granulated to obtain an adhesive.
[0065] Example 2
[0066] A method for preparing a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric includes the following steps:
[0067] Step S1: By weight, mix 85 parts PVC resin powder, 12 parts nitrile rubber, 7 parts plasticizer dioctyl adipate, 3.5 parts barium zinc stabilizer, 0.7 parts antioxidant 1010, 0.3 parts ultraviolet absorber UV-531, 0.3 parts antifungal and antibacterial agent, 0.3 parts acrylate processing aid ACR-201, 0.7 parts calcium stearate lubricant, 7 parts rutile titanium dioxide R-298, 0.7 parts pigment phthalocyanine blue BGS, 7 parts flame-retardant modified hollow glass microspheres, 1.2 parts vulcanizing agent dicumyl peroxide, 1.7 parts activator zinc oxide, and 1.0 part accelerator triallyl isocyanurate in three stages of intensive mixing.
[0068] First stage: PVC resin, nitrile rubber, plasticizer and additives are mixed at 90°C for 4 minutes and then cooled to 65°C;
[0069] Second stage: Add flame-retardant modified hollow glass microspheres, rutile titanium dioxide R-298 and pigment phthalocyanine blue BGS, stir evenly and heat to 115℃.
[0070] Third stage: Add the remaining components and mix at 160℃ for 6 minutes. Then cool down to 115℃ and add flame-retardant modified hollow glass microspheres. Stir evenly and immediately transfer to the calendering process; calender, cool, trim and roll to obtain the surface PVC film layer.
[0071] Step S2: Mix 95 parts of EPVC paste resin PCH-31, 55 parts of plasticizer TOTM and 43 parts of adhesive at high speed to form a paste slurry, and obtain the bottom adhesive slurry.
[0072] Step S3: Prepare a sample with a pore size of 0.03 mm and a basis weight of 200 g / m³. 2 Flame-retardant polyester woven fabric is impregnated with cyclophosphonitrile flame retardant solution, and after drying, the weight increases by 8.5%. Then, a base adhesive slurry is coated on its surface, and after drying, a PVC-coated flame-retardant polyester woven fabric is obtained.
[0073] Step S4: Apply the PVC film layer to the PVC-coated flame-retardant polyester woven fabric coated with the bottom adhesive paste, and hot-press the composite. The hot-pressing process is segmented pressing: the pre-pressing stage is at 0.7MPa pressure for 15s; the final pressing stage is at 3.8MPa pressure for 28s; use a parallel stripe embossing roller to emboss at 110℃ and 10MPa, with a texture depth of 0.15mm, then cool to 40℃, trim the edges and roll up to obtain a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric.
[0074] The method for synthesizing the antifungal and antibacterial agent in step S1 is as follows: 0.95 mol of phthalimide is dissolved in 580 mL of dichloromethane, 1.03 mol of trichloromethylsulfonyl chloride is slowly added dropwise, and the temperature is controlled to be less than or equal to 10 °C. 1.03 mol of triethylamine is added, the temperature is raised to 24 °C, the reaction is carried out for 5.3 h, the mixture is filtered and concentrated, and then recrystallized with ethanol to obtain the antifungal and antibacterial agent.
[0075] The preparation method of flame-retardant modified hollow glass microspheres in step S1 is as follows: 20-100 μm hollow glass microspheres are immersed in 6% sodium hydroxide solution and ultrasonically vibrated at 63℃ for 16 min to remove surface oil. Then, they are transferred to 8.5% hydrochloric acid solution and soaked at room temperature for 33 min to activate the silanol groups. After centrifugation and washing with deionized water until the conductivity of water is less than or equal to 4 μS / cm, they are vacuum dried at 65℃ for 2.2 h to obtain surface-activated hollow glass microspheres.
[0076] By weight, 16 parts ammonium polyphosphate and 6 parts aluminum hypophosphite were dissolved in 100 parts deionized water and 45 parts ethanol to prepare an atomizing agent. The surface-activated hollow glass microspheres were dynamically coated three times in a fluidized bed at an inlet air temperature of 70°C and an atomization pressure of 0.32 MPa, with each cycle dried at 5-minute intervals. The microspheres were then heat-treated at 102°C for 32 minutes to obtain flame-retardant grafted hollow glass microspheres.
[0077] Flame-retardant grafted hollow glass microspheres were spray-treated in a fluidized bed with an anhydrous ethanol solution containing 2.2% by mass of titanate coupling agent NDZ-201 and reacted at 63℃ for 22 min to obtain flame-retardant modified hollow glass microspheres.
[0078] The method for preparing the adhesive in step S3 is as follows:
[0079] 100 parts of chlorinated polypropylene HCPP-030 with a chlorine content of 29%, 9 parts of maleic anhydride, and 0.4 parts of dicumyl peroxide were melt-mixed in an internal mixer at 138°C, and then extruded and granulated to obtain an adhesive.
[0080] Example 3
[0081] A method for preparing a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric includes the following steps:
[0082] Step S1: By weight, mix 92 parts PVC resin powder, 14 parts nitrile rubber, 8 parts plasticizer dioctyl adipate, 4 parts barium zinc stabilizer, 0.8 parts antioxidant 1010, 0.4 parts ultraviolet absorber UV-531, 0.35 parts mildew and antibacterial agent, 0.35 parts acrylate processing aid ACR-201, 0.9 parts calcium stearate lubricant, 8 parts rutile titanium dioxide R-298, 0.9 parts pigment phthalocyanine blue BGS, 8 parts flame-retardant modified hollow glass microspheres, 1.4 parts vulcanizing agent dicumyl peroxide, 1.9 parts activator zinc oxide, and 1.1 parts accelerator triallyl isocyanurate in three stages of intensive mixing.
[0083] First stage: PVC resin, nitrile rubber, plasticizer and additives are mixed at 95°C for 4.5 min and then cooled to 68°C;
[0084] Second stage: Add flame-retardant modified hollow glass microspheres, rutile titanium dioxide R-298 and pigment phthalocyanine blue BGS, stir evenly and heat to 118℃.
[0085] Third stage: Add the remaining components and mix at 150℃ for 10 minutes. Then cool down to 100℃ and add flame-retardant modified hollow glass microspheres. Stir evenly and immediately transfer to the calendering process. Calender, cool, trim and roll to obtain the surface PVC film layer.
[0086] Step S2: Mix 110 parts of EPVC paste resin PCH-31, 60 parts of plasticizer TOTM and 46 parts of adhesive at high speed to form a paste slurry, and obtain the bottom adhesive slurry.
[0087] Step S3: Prepare a sample with a pore size of 0.02 mm and a basis weight of 300 g / m³. 2 Flame-retardant polyester woven fabric is impregnated with cyclophosphonitrile flame retardant solution, and after drying, the weight increases by 9%. Then, a base adhesive slurry is coated on its surface, and after drying, PVC-coated flame-retardant polyester woven fabric is obtained.
[0088] Step S4: Apply the PVC film layer to the surface of the PVC-coated flame-retardant polyester woven fabric coated with the bottom adhesive paste, and hot-press the composite. The hot-pressing process is segmented pressing: the pre-pressing stage is at 0.9MPa pressure for 18s; the final pressing stage is at 4.5MPa pressure for 35s; use a parallel stripe embossing roller to emboss at 130℃ and 12MPa, with a texture depth of 0.18mm, then cool to 40℃, trim the edges and roll up to obtain a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric.
[0089] The method for synthesizing the antifungal and antibacterial agent in step S1 is as follows: 1.05 mol of phthalimide is dissolved in 620 mL of dichloromethane, and 1.08 mol of trichloromethylsulfonyl chloride is slowly added dropwise while maintaining the temperature at 10°C or less. Then, 1.08 mol of triethylamine is added, the temperature is raised to 26°C, and the reaction is carried out for 5.5 h. After filtration and concentration, the mixture is recrystallized from ethanol to obtain the antifungal and antibacterial agent.
[0090] The preparation method of flame-retardant modified hollow glass microspheres in step S1 is as follows: 20-100 μm hollow glass microspheres are immersed in 7% sodium hydroxide solution and ultrasonically vibrated at 66℃ for 18 min to remove surface oil. Then, they are transferred to 9% hydrochloric acid solution and soaked at room temperature for 36 min to activate the silanol groups. After centrifugation and washing with deionized water until the conductivity of water is less than or equal to 3 μS / cm, they are vacuum dried at 75℃ for 2.6 h to obtain surface-activated hollow glass microspheres.
[0091] By weight, 18 parts ammonium polyphosphate and 7 parts aluminum hypophosphite were dissolved in 100 parts deionized water and 50 parts ethanol to prepare an atomizing agent. The surface-activated hollow glass microspheres were dynamically coated three times in a fluidized bed at an inlet air temperature of 70°C and an atomization pressure of 0.34 MPa, with a drying interval of 5 minutes between each coating. The microspheres were then heat-treated at 108°C for 36 minutes to obtain flame-retardant grafted hollow glass microspheres.
[0092] Flame-retardant grafted hollow glass microspheres were spray-treated in a fluidized bed with an anhydrous ethanol solution containing 2.7% by mass of titanate coupling agent NDZ-201 and reacted at 68℃ for 27 min to obtain flame-retardant modified hollow glass microspheres.
[0093] The method for preparing the adhesive in step S3 is as follows:
[0094] 100 parts of chlorinated polypropylene HCPP-030 with a chlorine content of 31%, 10 parts of maleic anhydride, and 0.6 parts of dicumyl peroxide were melt-mixed in an internal mixer at 145°C, and then extruded and granulated to obtain an adhesive.
[0095] Example 4
[0096] A method for preparing a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric includes the following steps:
[0097] Step S1: By weight, mix 96 parts PVC resin powder, 13.5 parts nitrile rubber, 9 parts plasticizer dioctyl adipate, 4.5 parts barium zinc stabilizer, 0.9 parts antioxidant 1010, 0.45 parts ultraviolet absorber UV-531, 0.3 parts mildew and antibacterial agent, 0.3 parts acrylate processing aid ACR-201, 0.8 parts calcium stearate lubricant, 9 parts rutile titanium dioxide R-298, 0.8 parts pigment phthalocyanine blue BGS, 9 parts flame-retardant modified hollow glass microspheres, 1.3 parts vulcanizing agent dicumyl peroxide, 1.8 parts activator zinc oxide, and 0.9 parts accelerator triallyl isocyanurate in three stages of intensive mixing.
[0098] First stage: PVC resin, nitrile rubber, plasticizer and additives are mixed at 85°C for 4 minutes and then cooled to 63°C;
[0099] Second stage: Add flame-retardant modified hollow glass microspheres, rutile titanium dioxide R-298 and pigment phthalocyanine blue BGS, stir evenly and heat to 112℃.
[0100] Third stage: Add the remaining components and mix at 150℃ for 8 minutes. Then cool down to 110℃ and add flame-retardant modified hollow glass microspheres. Stir evenly and immediately transfer to the calendering process; calender, cool, trim and roll to obtain the surface PVC film layer.
[0101] Step S2: Mix 105 parts of EPVC paste resin PCH-31, 65 parts of plasticizer TOTM and 48 parts of adhesive at high speed to form a paste slurry, and obtain the bottom adhesive slurry.
[0102] Step S3: Prepare a sample with a pore size of 0.04 mm and a basis weight of 400 g / m³. 2 Flame-retardant polyester woven fabric is impregnated with cyclophosphonitrile flame retardant solution, and after drying, the weight increases by 9.5%. Then, a base adhesive paste is coated on its surface, and after drying, PVC-coated flame-retardant polyester woven fabric is obtained.
[0103] Step S4: Apply the PVC film layer to the surface of the PVC-coated flame-retardant polyester woven fabric coated with the bottom adhesive paste, and hot-press the composite. The hot-pressing process is segmented pressing: the pre-pressing stage is at 0.8MPa pressure for 16s; the final pressing stage is at 4.0MPa pressure for 30s; use a parallel stripe embossing roller to emboss at 120℃ and 13MPa, with a texture depth of 0.16mm, then cool to 40℃, trim the edges and roll up to obtain a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric.
[0104] The method for synthesizing the antifungal and antibacterial agent in step S1 is as follows: 1.08 mol of phthalimide is dissolved in 600 mL of dichloromethane, and 1.06 mol of trichloromethylsulfonyl chloride is slowly added dropwise while maintaining the temperature at 10°C or less. Then, 1.06 mol of triethylamine is added, the temperature is raised to 27°C, and the reaction is carried out for 5.2 h. After filtration and concentration, the mixture is recrystallized from ethanol to obtain the antifungal and antibacterial agent.
[0105] The preparation method of flame-retardant modified hollow glass microspheres in step S1 is as follows: 20-100 μm hollow glass microspheres are immersed in 6.5% sodium hydroxide solution and ultrasonically vibrated at 68℃ for 17 min to remove surface oil. Then, they are transferred to 8.8% hydrochloric acid solution and soaked at room temperature for 35 min to activate the silanol groups. After centrifugation and washing with deionized water until the conductivity of water is less than or equal to 4 μS / cm, they are vacuum dried at 70℃ for 2.4 h to obtain surface-activated hollow glass microspheres.
[0106] By weight, 17 parts ammonium polyphosphate and 6.5 parts aluminum hypophosphite were dissolved in 100 parts deionized water and 48 parts ethanol to prepare an atomizing agent. The surface-activated hollow glass microspheres were dynamically coated three times in a fluidized bed at an inlet air temperature of 70°C and an atomization pressure of 0.33 MPa, with a drying interval of 5 minutes between each coating. The microspheres were then heat-treated at 105°C for 34 minutes to obtain flame-retardant grafted hollow glass microspheres.
[0107] Flame-retardant grafted hollow glass microspheres were spray-treated in a fluidized bed with an anhydrous ethanol solution containing 2.4% by mass of titanate coupling agent NDZ-201 and reacted at 65℃ for 25 min to obtain flame-retardant modified hollow glass microspheres.
[0108] The method for preparing the adhesive in step S3 is as follows:
[0109] 100 parts of chlorinated polypropylene HCPP-030 with a chlorine content of 30%, 11 parts of maleic anhydride, and 0.5 parts of dicumyl peroxide were melt-mixed in an internal mixer at 142°C, and then extruded and granulated to obtain an adhesive.
[0110] Example 5
[0111] A method for preparing a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric includes the following steps:
[0112] Step S1: By weight, mix 100 parts PVC resin powder, 15 parts nitrile rubber, 10 parts plasticizer dioctyl adipate, 5 parts barium zinc stabilizer, 1 part antioxidant 1010, 0.5 parts ultraviolet absorber UV-531, 0.4 parts mildew and antibacterial agent, 0.4 parts acrylate processing aid ACR-201, 1 part calcium stearate lubricant, 10 parts rutile titanium dioxide R-298, 1 part pigment phthalocyanine blue BGS, 10 parts flame-retardant modified hollow glass microspheres, 1.5 parts vulcanizing agent dicumyl peroxide, 2 parts activator zinc oxide, and 1.2 parts accelerator triallyl isocyanurate in three stages of intensive mixing.
[0113] First stage: PVC resin, nitrile rubber, plasticizer and additives are mixed at 100°C for 5 minutes and then cooled to 70°C;
[0114] Second stage: Add flame-retardant modified hollow glass microspheres, rutile titanium dioxide R-298 and pigment phthalocyanine blue BGS, stir evenly and heat to 120℃.
[0115] Third stage: Add the remaining components and mix at 160℃ for 5 minutes. Then cool down to 100℃ and add flame-retardant modified hollow glass microspheres. Stir evenly and immediately transfer to the calendering process. Calender, cool, trim and roll to obtain the surface PVC film layer.
[0116] Step S2: Mix 120 parts of EPVC paste resin PCH-31, 70 parts of plasticizer TOTM and 50 parts of adhesive at high speed to form a paste slurry, and obtain the bottom adhesive slurry.
[0117] Step S3: Prepare a sample with a pore size of 0.01 mm and a basis weight of 500 g / m³. 2 Flame-retardant polyester woven fabric is impregnated with cyclophosphonitrile flame retardant solution, and after drying, the weight increases by 10%. Then, a base adhesive slurry is coated on its surface, and after drying, a PVC-coated flame-retardant polyester woven fabric is obtained.
[0118] Step S4: Apply the PVC film layer to the surface of the PVC-coated flame-retardant polyester woven fabric coated with the bottom adhesive paste, and hot-press the composite. The hot-pressing process is segmented pressure: the pre-pressing stage is at 1.0MPa pressure for 20s; the final pressing stage is at 5.0MPa pressure for 40s; use a parallel stripe embossing roller to emboss at 150℃ and 15MPa, with a texture depth of 0.20mm, then cool to 40℃, trim the edges and roll up to obtain a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric.
[0119] The method for synthesizing the antifungal and antibacterial agent in step S1 is as follows: 1.1 mol of phthalimide is dissolved in 650 mL of dichloromethane, and 1.1 mol of trichloromethylsulfonyl chloride is slowly added dropwise while controlling the temperature to be less than or equal to 10 °C. 1.1 mol of triethylamine is added, the temperature is raised to 28 °C, and the reaction is carried out for 6 h. After filtration and concentration, the mixture is recrystallized with ethanol to obtain the antifungal and antibacterial agent.
[0120] The preparation method of flame-retardant modified hollow glass microspheres in step S1 is as follows: 20-100μm hollow glass microspheres are immersed in 8% sodium hydroxide solution and ultrasonically vibrated at 70℃ for 20min to remove surface oil stains. Then, they are transferred to 10% hydrochloric acid solution and soaked at room temperature for 40min to activate the silanol groups. After centrifugation and washing with deionized water until the conductivity of water is less than or equal to 2μS / cm, they are vacuum dried at 80℃ for 3h to obtain surface-activated hollow glass microspheres.
[0121] By weight, 20 parts ammonium polyphosphate and 8 parts aluminum hypophosphite were dissolved in 100 parts deionized water and 60 parts ethanol to prepare an atomizing agent. The surface-activated hollow glass microspheres were dynamically coated three times in a fluidized bed at an inlet air temperature of 70°C and an atomization pressure of 0.35 MPa, with a drying interval of 5 minutes between each coating. The microspheres were then heat-treated at 110°C for 40 minutes to obtain flame-retardant grafted hollow glass microspheres.
[0122] Flame-retardant grafted hollow glass microspheres were spray-treated in a fluidized bed with an anhydrous ethanol solution containing 3% by mass titanate coupling agent NDZ-201 and reacted at 70℃ for 30 min to obtain flame-retardant modified hollow glass microspheres.
[0123] The method for preparing the adhesive in step S3 is as follows:
[0124] 100 parts of chlorinated polypropylene HCPP-030 with a chlorine content of 32%, 12 parts of maleic anhydride, and 0.7 parts of dicumyl peroxide were melt-mixed in an internal mixer at 150°C, and then extruded and granulated to obtain an adhesive.
[0125] Comparative Example 1
[0126] The difference from Example 1 is that flame-retardant modified hollow glass microspheres were not used.
[0127] Comparative Example 2
[0128] The difference from Example 1 is that a common isothiazolinone antifungal and antibacterial agent is used.
[0129] Comparative Example 3
[0130] The difference from Example 1 is that hollow glass microspheres were used.
[0131] Comparative Example 4
[0132] The difference from Example 1 is that the adhesive in step S2 is an acrylic adhesive.
[0133] Comparative Example 5
[0134] The difference from Example 1 is that segmented internal mixing was not used; all components were mixed at 120°C for 10 minutes.
[0135] Comparative Example 6
[0136] The difference from Example 1 is that the flame-retardant modified hollow glass microspheres were added in excess, at 15 parts.
[0137] Comparative Example 7
[0138] The difference from Example 1 is that step S3: The pore size is 0.01 mm, and the basis weight is 500 g / m³. 2 Flame-retardant polyester woven fabric impregnated with cyclophosphonitrile flame retardant solution, increased in weight by 15% after drying.
[0139] Comparative Example 8
[0140] The difference from Example 1 is that nitrile rubber was added in excess, at 20 parts.
[0141] Comparative Example 9
[0142] The difference from Example 1 is that the amount of nitrile rubber added is too small, only 5 parts.
[0143] Comparative Example 10
[0144] The difference from Example 1 is that step S1 was not intensively mixed.
[0145] Comparative Example 11
[0146] The difference from Example 1 is that the hot pressing process was not segmented, and the entire process was carried out at a pressure of 3.0 MPa for 30 seconds.
[0147] Comparative Example 12
[0148] The difference from Example 1 is that the chlorinated polypropylene has a chlorine content of 35%.
[0149] Performance testing:
[0150] Density testing: Performance calculation using the water displacement method;
[0151] Interlayer peel strength testing: The main testing methods refer to GB / T 2792-2014;
[0152] Flame retardant performance testing: Refer to GB / T 2406.2-2009 "Determination of burning behavior of plastics by oxygen index method" and GB / T2408-2021 "Determination of burning performance of plastics by horizontal and vertical methods";
[0153] Sound insulation effect test: The 30×30cm sample was tightly fixed to the opening of the custom sound insulation box. 85dB white noise was placed outside the box. Inside the box, the sound pressure value L1 transmitted through the sample was measured with a decibel meter close to the back of the sample. The sound insulation volume TL=85-L1 (dB). Three measurements were taken at the same point and the average was taken.
[0154] The detection performance is shown in Table 1.
[0155]
[0156] This embodiment of the solution constructs a three-dimensional interlocking structure through the chemical bonding interface between the nitrile rubber vulcanization network and the flame-retardant microspheres. Combined with the in-situ esterification reaction of the adhesive maleic anhydride groups and polyester fibers, as well as the control of process parameters in the preparation process, it is better than commercially available products in terms of density, peel strength, acoustic scattering efficiency and flame retardancy.
[0157] Compared to Example 1, Comparative Example 1, due to the lack of flame-retardant modified hollow glass microspheres, resulted in the disappearance of the sound wave scattering interface and the breakage of the phosphorus-nitrogen synergistic flame retardant, leading to a double failure in sound insulation and flame retardancy; Comparative Example 2, using a common antifungal agent, suffered from molecular migration that disrupted the flame retardant continuity and weakened the matrix bonding force; in Comparative Example 3, the hydroxyl groups on the surface of the unmodified hollow glass microspheres initiated phase separation, creating sound energy transmission channels and stress weaknesses, resulting in even worse flame retardant performance; in Comparative Example 4, the mismatch between the acrylic adhesive and polyester polarity led to curing shrinkage and cracking of the interlayer interface; in Comparative Example 5, the lack of segmented mixing caused premature decomposition of the vulcanizing agent, and the nitrile rubber failed to form a cross-linked network, thus losing its toughening and buffering function, resulting in poorer sound insulation; Comparative Example 6... Excessive microspheres disrupted the continuous phase structure of PVC. Although the sound insulation, density, and flame retardancy were good, the peel strength was low. In Comparative Example 7, excessive weight gain of the base fabric caused the flame retardant to crystallize and become brittle, and fiber breakage during embossing damaged the sound wave dissipation path. In Comparative Example 8, excessive nitrile rubber competed for plasticizers, causing matrix hardening. In Comparative Example 9, insufficient rubber led to the breakage of the stress transmission network, both of which disrupted the rigidity-toughness balance. In Comparative Example 10, lack of internal mixing caused flame retardant agglomeration, forming heat conduction hotspots and interfacial voids. In Comparative Example 11, constant pressure hot pressing caused the adhesive melt to be extruded, damaging the chemical bond layer. In Comparative Example 12, the rigidity of the high-chlorine adhesive molecular chain mismatched with the deformation of the base fabric, and internal stress tore the interface during cooling. All comparative examples ultimately resulted in the loss of the multifunctional coupling effect of the materials due to the disruption of the PVC-rubber-microsphere three-phase synergistic system and the temperature-pressure-time process matching.
[0158] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric, characterized in that, Includes the following steps: Step S1: By weight, mix 80-100 parts of PVC resin powder, 10-15 parts of nitrile rubber, 5-10 parts of plasticizer, 3-5 parts of stabilizer, 0.5-1 part of antioxidant, 0.2-0.5 parts of ultraviolet absorber, 0.2-0.4 parts of mildew and antibacterial agent, 0.2-0.4 parts of processing aid, 0.5-1 part of lubricant, 5-10 parts of titanium dioxide, 0.5-1 part of pigment, 5-10 parts of flame-retardant modified hollow glass microspheres, 1.0-1.5 parts of vulcanizing agent, 1.5-2.0 parts of activator, and 0.8-1.2 parts of accelerator, calender, cool, trim, and roll to obtain the surface PVC film layer; Step S2: Mix 80-120 parts of EPVC paste resin, 50-70 parts of plasticizer and 40-50 parts of adhesive at high speed to form a paste slurry, and obtain the bottom adhesive slurry. Step S3: Impregnate the flame-retardant polyester woven fabric with cyclophosphonitrile flame retardant solution, dry it and gain 8-10% weight, then coat its surface with a base adhesive paste, and dry it to obtain PVC coated flame-retardant polyester woven fabric. Step S4: Apply the surface PVC film layer and the PVC-coated flame-retardant polyester woven fabric coated with the bottom adhesive paste to the surface, hot press and laminate, and form a brushed texture to obtain a flame-retardant, lightweight, and high-sound-insulating composite PVC brushed fabric.
2. The preparation method of the flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric as described in claim 1, characterized in that, In step S1, the plasticizer is dioctyl adipate, the stabilizer is barium zinc stabilizer, the antioxidant is antioxidant 1010, the ultraviolet absorber is UV-531, the processing aid is acrylate processing aid ACR-201, the lubricant is calcium stearate, the vulcanizing agent is dicumyl peroxide, the activator is zinc oxide, and the accelerator is triallyl isocyanurate.
3. The preparation method of the flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric as described in claim 1, characterized in that, In step S1, the mixing process includes three stages: First stage: PVC resin, nitrile rubber, plasticizer, stabilizer, antioxidant, ultraviolet absorber, mildew and antibacterial agent, processing aid and lubricant are mixed at 80-100℃ for 3-5 minutes and cooled to 60-70℃; Second stage: Add flame-retardant modified hollow glass microspheres, titanium dioxide and pigments, stir evenly and heat to 110-120℃; Third stage: Add the remaining components and mix at 150-160℃ for 5-10 minutes. Then cool down to 100-120℃, add flame-retardant modified hollow glass microspheres, stir evenly, and immediately transfer to the calendering process.
4. The preparation method of the flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric as described in claim 1, characterized in that, The method for synthesizing the antifungal and antibacterial agent in step S1 is as follows: 0.9-1.1 mol of phthalimide is dissolved in 550-650 mL of dichloromethane, and 1-1.1 mol of trichloromethylsulfonyl chloride is slowly added dropwise while controlling the temperature to ≤10℃. Then, 1-1.1 mol of triethylamine is added, the temperature is raised to 23-28℃, and the reaction is carried out for 5-6 hours. After filtration and concentration, the mixture is recrystallized with ethanol to obtain the antifungal and antibacterial agent.
5. The preparation method of the flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric as described in claim 1, characterized in that, The preparation method of flame-retardant modified hollow glass microspheres in step S1 is as follows: hollow glass microspheres of 20-100 μm are washed with alkali, acid, and then cleaned and dried to obtain surface-activated hollow glass microspheres. Surface-activated hollow glass microspheres were dynamically coated by multiple cycles of atomization, followed by heat treatment at 100-110℃ for 30-40 minutes to obtain flame-retardant grafted hollow glass microspheres. The atomizing agent used in the atomization method consists of the following components by mass: 15-20 parts ammonium polyphosphate, 5-8 parts aluminum hypophosphite solution, and 40-60 parts ethanol. Finally, the flame-retardant grafted hollow glass microspheres were modified using a titanate coupling agent to obtain flame-retardant modified hollow glass microspheres.
6. The preparation method of the flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric as described in claim 1, characterized in that, The method for preparing the adhesive in step S3 is as follows: 100 parts of chlorinated polypropylene with a chlorine content of 28-32%, 8-12 parts of maleic anhydride, and 0.3-0.7 parts of dicumyl peroxide are melt-mixed in an internal mixer at 135-150°C, and then extruded and granulated to obtain an adhesive.
7. The preparation method of the flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric as described in claim 1, characterized in that, Flame-retardant polyester woven fabrics have a pore size ≤0.05mm and a basis weight of 100-500g / m². 2 .
8. The preparation method of the flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric as described in claim 1, characterized in that, The hot-pressing composite process conditions are: 120-160℃, 0.5-5.0MPa for 30-60s; the hot-pressing composite process is segmented pressurization: the pre-pressing stage is maintained at 0.5-1MPa for 10-20s to remove interlayer bubbles; the final pressing stage is maintained at 3-5.0MPa for 20-40s.
9. The preparation method of the flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric as described in claim 1, characterized in that, The process of forming the brushed texture is as follows: embossing with a parallel stripe embossing roller at 80-150℃ and 8-15MPa, with a texture depth ≥0.1mm, followed by cooling to 40℃, trimming the edges and winding up to obtain flame-retardant, lightweight, and high-sound-insulating composite PVC brushed fabric.
10. A flame-retardant, lightweight, high-sound-insulating composite PVC filament fabric prepared by a method according to any one of claims 1-9.
Citation Information
Patent Citations
A drone runway and laying device made of high-pressure airtight fabric
CN114808598B
Cited By
Special repairing adhesive sticker for salt pond covering film, preparation method and application thereof
CN121610199A